IMPLEMENTATION OF THE DISASTER RESILIENT VILLAGE PROGRAM THROUGH THE HEXAHELIX APPROACH IN BUNGURASIH VILLAGE, WARU DISTRICT - Audy Arilia, Syavira; Mursyidah, Lailul (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the implementation of the Disaster Resilient Village (Destana) program in Bungurasih Village, Waru District, Sidoarjo Regency, focusing on efforts to build community capacity in disaster mitigation through a collaborative framework. Method: A descriptive qualitative approach was employed, utilizing triangulation techniques of interviews, observations, and documentation, with analysis guided by the Hexahelix collaboration model and Edward III’s policy implementation dimensions of communication, resources, disposition, and bureaucratic structure. Results: The findings indicate that although Bungurasih Village has not been formally integrated into the BPBD Destana system, disaster management activities have been implemented collaboratively and participatively. The village government actively fosters partnerships with MSMEs through Bumdes and leverages social media for information dissemination. Community participation is evident in evacuation and logistics, yet engagement from academics, the business sector, and formal mass media remains limited. Key obstacles include inadequate emergency communication systems, limited resources, and bureaucratic delays in logistics. Novelty: This study highlights the application of the Hexahelix approach as a practical and adaptive model for strengthening disaster resilience at the village level, offering new insights into the integration of local governance, community participation, and cross-sector collaboration in disaster risk reduction.